Web based integrated food ordering system - Chin Ming, Lee (2013)
As the internet technology has become essential for human life, diversity of web based system or online system has been created to fulfill increasing customer demand. Nowadays, variety of existing manual system was replaced by a web-based system due to the time-consuming manual systems and unsolvable limitations appeared. In this paper, a web based ordering system is proposed for replacing existing manual system. This system will allowed user to make order, updating menu, uploading file, submitting document and so on. The main user requirement collection method is by interviewing users and stakeholders. Based on the research, mostly web based system has been used for business and education that beneficial to business people, students and lecturers. Therefore, lecturers and students can easily access the web based system through internet by using computer or mobile device to get the latest information or announcement. On these few years, the development of system has been dramatically influenced by web technology as a platform for different types of system. The web based system development has been growing due to the highly recommended from user in order to replace the non-web based system or manually system.